2019
DOI: 10.3390/app9091812
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Shield Attitude Change on Shield–Soil Interaction

Abstract: The mechanism of shield–soil interaction and multi-phase equilibrium control theory in shield tunneling process still lack sufficient understanding. Aiming at this problem, with the improved calculation method of loose earth pressure, the initial boundary problem of shield attitude calculation was solved. Based on the ground reaction curve, the shield–soil interaction was simulated by the equivalent springs, and the displacement of surrounding soil was calculated during the change of the shield attitude. Then,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Shen et al 23 concluded that shield-soil interaction affects the change of the shield attitude to some extent; they found that it could better reflect the load because the system attitude is taken into account. Via the establishment of a group-adjustable thrust hydraulic system, the change of the hydraulic cylinder thrust has been used to reflect the sudden change of the external load.…”
Section: Introductionmentioning
confidence: 99%
“…Shen et al 23 concluded that shield-soil interaction affects the change of the shield attitude to some extent; they found that it could better reflect the load because the system attitude is taken into account. Via the establishment of a group-adjustable thrust hydraulic system, the change of the hydraulic cylinder thrust has been used to reflect the sudden change of the external load.…”
Section: Introductionmentioning
confidence: 99%
“…The limitation of numerical methods, however, lies in the evaluation of the input parameters involved in the constitutive models (Ninić et al, 2017). Besides, implementing all operational factors in numeric simulations simultaneously is challenging (Khisamitov and Meschke, 2018;Ren et al, 2018;Shen et al, 2019). However, these operational factors are significant for estimation of tunneling-induced ground surface settlement.…”
Section: Introductionmentioning
confidence: 99%
“…Ren et al (2018) (Ren et al, 2018) evaluated the gap area between the double-O-tube (DOT) shield machine by considering pitching, yawing, and rolling features. Shen et al (2019) considered pitching angle and yawing angle to investigate shield-soil interactions and proposed a prediction model. Owing to the complexity of shield-soil interactions, datadriven models were triggered using artificial intelligence methods (Cho, 2009;Ochmański et al, 2015;Chen et al, 2016;Pooya Nejad and Jaksa, 2017;Qi and Tang, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the increasingly tense urban space, it is inevitable for an urban shield tunnel to cross under and side through the existing building structure. e disturbance impact on the surrounding building structure is a problem that must be considered in the shield construction of urban subway tunnel; aiming at the settlement disturbance analysis of surrounding buildings caused by shield construction of urban subway tunnel, scholars have analyzed such problems from the perspectives of construction monitoring [1][2][3], theoretical analysis [4][5][6][7][8], and numerical simulation [9][10][11][12][13]31]. ere are many related research results, most of which are lateral disturbance analysis of straight-line section shield, while there is less analysis on the disturbance of existing building structure caused by the construction of turning shield tunnel, the interaction mechanism between turning shield tunnel excavation and existing buildings is more complex, which is affected by turning radius, advance excavation volume, ground conditions, tunnel structural characteristics, relative space position between shield and tunnel, type of shield machine, shield construction parameters, and whole process [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%